(untitled) (Journal of the College of Basic Education, 2025)
Long-range shooting by backline players requires high-precision skills and speed due to the distance and the presence of defenders and goalkeeper in front of the player, which requires accuracy in shooting on goal. Through this, the researcher found it necessary to study the relationship between the biokinetic variables of this skill for backline players and to know the jump strength, performance speed and some other variables for players who perform long-range shooting. The study aimed to: Identify the values of the ball trajectory and the longitudinal and transverse axes for the preparation and shooting phases when performing the long-range shooting skill. Identify the difference between the distance from the vertical (longitudinal) axis and the ball launch angle when performing the shooting skill for the research sample. Research Methodology: The researcher used the descriptive survey method to solve the research problem. The researcher chose the research sample selected intentionally by the researcher, which amounted to (5)players The representative players (right forearm) of the team were selected. The percentage of the research sample was 27.78%. The researcher used the Dart Fish program to extract the kinetic variables. After processing the data on the computer according to the statistical program SPSS Ver. 10, a set of conclusions were reached, the most important of which are: the appearance of curves in the ball’s path, especially after the ball deviates from the vertical (longitudinal) axis, which indicates a lack of smooth performance, and thus the ball exits from the front of the head, which increases the angle of exit and entry of the ball, thus increasing the flight arc of the ball and increasing its flight time. There is a significant correlation between the dimension of the vertical (longitudinal) axis and the ball launch angle for the research sample. The most important recommendations: the need to emphasize mechanical characteristics when performing the straightening skill, especially the proximity of the ball to the longitudinal axis, which leads to the ball exiting at a large angle. Increasing the angle of the shoulder joint to obtain an appropriate exit angle for the ball and for the ball to enter at a suitable angle.